INFORMATION MODEL OF DEVELOPMENT OF RAILWAY TRANSPORT INFRASTRUCTURE IN THE SYSTEM OF MULTIMODAL PASSENGER TRANSPORTATION - Поздняков, Андрій Анатолійович; Мироненко, Віктор Кімович; Позднякова, Ольга Олександрівна (Science-based technologies, 2019)
In resolving the scientific task of developing an information model for the development of railway transport infrastructure in the system of multimodal passenger transportation, it is important to recognize the best practices of passenger transportation of the countries of the European Union (EC), in particular the UK experience, which accounts for 20% of all passenger traffic of the EU. Clearly separated roles of the system operator within the infrastructure operator, acting as the focal point with all participants in the process of transport, is of great scientific and practical importance as it helps to achieve the research goal - to build an optimal model for the interaction of existing and potential market participants: infrastructure operators, carriers, passengers and government and public organizations. In the model of the development of railway transport infrastructure of Ukraine, it is proposed to separate the system operator from infrastructure operators and carriers for the purpose of qualitative, operational planning of trains and avoiding a conflict of interest in providing access to lines (including future high-speed lines), a coherent train schedule, change management, and safe integration into new lines. It is substantiated that under such conditions only a systemic view of all the challenges of passenger transportation will be able to provide high-quality analysis for the transport management system, operators and potential investors. Creating a separate system operator enables you to offer a completely different quality analysis to support rational and efficient management decisions in the field of passenger transportation.